"Iniuria post mortem testatoris" w prawie rzymskim okresu klasycznego w świetle koncepcji "iniuria indirecta" - Nowicka, Dobromiła (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The aim of the article is to analyse regulations concerning injury to personality associated with deeds committed directly against a corpse, funeral rites or a testator’s reputation. The author’s reflections focus on the classification of these infringements as indirect injury to the testator’s reputation as proposed in the doctrine. Apart from undeniable shared features of iniuria post mortem testatoris and (other) cases of iniuria indirecta, we can point to significant differences stemming primarily from a lack of possibility — even if only potential — of direct iniuria if a deed is committed against a corpse or the testator’s reputation. This feature, in turn, seems to be present in all (other) cases classified as indirect iniuria. It should also be stressed that in the case of iniuria post mortem testatoris it is impossible to apply any of the criteria indicated as the basis for regarding specific behaviour as a slight to the reputation not only directly of the injured party but also other individuals whose reputation is injured only indirectly as a result of the perpetrator’s actions
Keywords: prawo rzymskie; znieważenie zwłok; prawo; wymiar sprawiedliwości